Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1093/carcin/23.11.1839
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacogenetic study to investigate the role of dietary carcinogens in the etiology of colorectal cancer

Abstract: Susceptibility to colorectal cancer, one of the most common forms of cancer in the Western world, has been associated with several environmental and dietary risk factors. Dietary exposure to food derived heterocyclic amine carcinogens and polycyclic aromatic hydrocarbons have been proposed as specific risk factors. Many polymorphic Phase I and Phase II drug metabolizing enzymes are responsible for the metabolism and disposition of these compounds and it is therefore possible that inheritance of specific alleli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
163
4
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(190 citation statements)
references
References 59 publications
17
163
4
6
Order By: Relevance
“…Furthermore, GSTM1 null genotype carriers are at a greater risk of developing colorectal malignancies. The results of this study are in agreement with those of numerous studies that have reported a significant effect of the GSTM1 null genotype on susceptibility to colorectal cancer (Sachse et al, 2002;Huang et al, 2006;Csejtei et al, 2008;Hlavata et al, 2010;Cai et al, 2014;Teng et al, 2014). The incidence of the null genotype in the current study was higher than that in similar studies that reported significant results (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, GSTM1 null genotype carriers are at a greater risk of developing colorectal malignancies. The results of this study are in agreement with those of numerous studies that have reported a significant effect of the GSTM1 null genotype on susceptibility to colorectal cancer (Sachse et al, 2002;Huang et al, 2006;Csejtei et al, 2008;Hlavata et al, 2010;Cai et al, 2014;Teng et al, 2014). The incidence of the null genotype in the current study was higher than that in similar studies that reported significant results (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…The results were similar to that from our analysis of dietary methyl status (P test for interaction >0.13; data not shown). Because this analysis of interaction with dietary methyl status was based on grouping the variant carriers, and the main effect of MTHFR Ala 222 Val has been observed to behave in a recessive manner, we also conducted this analysis with Vitamin B 12 is transported by TCN II and is a cofactor to MTR, the function of which is related to MTRR and BHMT, thus, we examined whether total vitamin B 12 intake (including dietary and supplemental sources) modified the associations for BHMT Arg 239 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) and nested case-control studies (10,(46)(47)(48). In addition, our finding that the inverse association was stronger for colon cancers versus rectal cancers was consistent with some (47,48), although not all previous studies (38,40,46).…”
Section: Resultsmentioning
confidence: 99%
“…Frequencies of both the 677T and 1298C alleles are generally in the range of 30-35% in Caucasians. [11][12][13][14][15][16][17][18][19] The relatively lower frequency of the 1298C allele makes it somewhat difficult to study the relation of MTFHR A1298C to colorectal cancer in Japanese.…”
Section: Discussionmentioning
confidence: 99%
“…13,14) However, other case-control studies have failed to substantiate a protective association with the 677TT genotype in various countries, including the United States. [15][16][17][18][19][20][21] Few studies have addressed the association between the MTHFR A1298C polymorphism and colorectal cancer. [14][15][16]22) Of these, only one study showed a decreased risk of colorectal cancer associated with the 1298CC genotype.…”
Section: )mentioning
confidence: 99%